2008
DOI: 10.1111/j.1460-9568.2008.06230.x
|View full text |Cite
|
Sign up to set email alerts
|

The forced swimming‐induced behavioural immobility response involves histone H3 phospho‐acetylation and c‐Fos induction in dentate gyrus granule neurons via activation of the N‐methyl‐d‐aspartate/extracellular signal‐regulated kinase/mitogen‐ and stress‐activated kinase signalling pathway

Abstract: The hippocampus is involved in learning and memory. Previously, we have shown that the acquisition of the behavioural immobility response after a forced swim experience is associated with chromatin modifications and transcriptional induction in dentate gyrus granule neurons. Given that both N-methyl-D-aspartate (NMDA) receptors and the extracellular signal-regulated kinases (ERK) 1/2 signalling pathway are involved in neuroplasticity processes underlying learning and memory, we investigated in rats and mice wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
190
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(210 citation statements)
references
References 64 publications
16
190
2
2
Order By: Relevance
“…For instance, antidepressants are able to modulate glutamatergic neurotransmission (56), which is capable of activating intracellular mechanisms that culminate with the modulation of the epigenetic machinery (57,58). In fact, it was reported that exposure to stressful events and consequent increased release of glucocorticoids and glutamate (and NMDA activation) can result in the phosphorylation of ERK1/2 which form a complex with GR and induce transcription factors that culminate with the modulation of the epigenetic machinery (57,58). Therefore, antidepressants could ultimately target DNMT activity acutely by modulating glutamate-induced levels upon stress exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, antidepressants are able to modulate glutamatergic neurotransmission (56), which is capable of activating intracellular mechanisms that culminate with the modulation of the epigenetic machinery (57,58). In fact, it was reported that exposure to stressful events and consequent increased release of glucocorticoids and glutamate (and NMDA activation) can result in the phosphorylation of ERK1/2 which form a complex with GR and induce transcription factors that culminate with the modulation of the epigenetic machinery (57,58). Therefore, antidepressants could ultimately target DNMT activity acutely by modulating glutamate-induced levels upon stress exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic social defeat stress has been shown to alter acetylation and methylation of histones on the promoter regions of a number of genes in the nucleus accumbens (38,40) and anti-depressant treatment in this model has been shown to reverse some of these effects. Acute stress has been shown to have an impact on histone acetylation and phosphorylation levels in the hippocampal formation (15,41,42). It, therefore, seems that chromatin remodeling in the brain is likely to play a significant role in normal and pathogenic responses to stress and in the treatment of stressrelated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These circumstances foster both rapid and delayed (protein-synthesisdependent) synaptic delivery of AMPAR and/or NMDAR subunits [39,40,42,51]. A subsequent and/or additional pathway involves NMDAR-triggering of signaling cascades leading to (epi)genomic changes in gene transcription [14,[73][74][75]80], with at least one of these targets leading to increased probability of glutamate release [80]. In general, rapid effects are mediated by membrane-bound MRs or GRs, whereas delayed genomic effects are mediated by nuclear-localized GRs.…”
Section: Opinionmentioning
confidence: 99%
“…Specifically, evidence has been presented that glucocorticoid-induced enhancement of memory consolidation (as assessed in a forced swim test) took place through the activation of NMDARs and the downstream mitogen-activated protein kinase (MAPK) pathway, including activation of ERK (extracellular signal-regulated kinase)/MSK (mitogen and stress-activated protein kinase) and transcription factor Elk-1 in the dentate gyrus of the hippocampus [73][74][75]. Activation of this pathway was demonstrated to result in epigenetic changes including enhanced histone acetylation [73][74][75]. These epigenetic mechanisms were only efficient in the presence of activated GRs and they acted in synergy with NMDAR activation [74] (Figure 1e).…”
Section: Trends In Neurosciencesmentioning
confidence: 99%